Altered cast impression technique in the fabrication of metal frame partial dentures with distal extension: A case report - Sutiyo; Rezki Wahyuni Syamsuddin; Bahruddin Thalib; Muhammad Ikbal (Indonesian Journal of Prosthodontic, 2022)
Metal frame denture is a more ideal treatment than the conventional acrylic denture for its narrower, thinner, rigid, and harder material, so that the design can be made ideally. The aim of this case report is to demonstrate the treat-ment of an edentulous case using altered cast technique to improve support for a partial denture with distal exten-tension. A 48-year-old female patient came to the Halima Dg.Sikati Makassar with complaints of chewing difficulty and lacking of confidence due to the loss of all her maxillary teeth and part of her mandibular teeth. The patient had never worn any denture and had no history of systemic disease. The patient wanted to have a denture made to resto-re the appearance and mastication. Then a panoramic x-ray was performed on the patient. Radiological images ap-pear to be missing all teeth in the maxilla, available teeth: 33, 32, 31, 41, 42 and 43, no impacted teeth, no foreign bodies, no inflammation or neoplastic tissue, good bone density, residual the roots of teeth 15 and 28. The pre-pros-thetic treatment plan was carried out by scaling and extracting the remaining roots on teeth 15 and 28. The prostho-thodontic treatment plan was the manufacture of partial metal frame dentures using the altered case molding techni-que. Altered cast is a molding technique used in the saddle free end of removable partial dentures. This impression technique can produce master case with maximum tissue support, within the limits of physiological tolerance and can accurately record the relationship between the tooth and the residual ridge. It is concluded that metal frame par-tial denture with Alter cast impression technique provides better and stable denture.